KNOWLEDGE BUILDING IN CHEMISTRY TEXTBOOKS IN AN INDONESIAN SECONDARY EDUCATION CONTEXT : Synergy Between Legitimation Code Theory and Systemic Functional Linguistics - Yulizar Komarawan, - (2019)
Penelitian ini menyelidiki jenis-jenis pengetahuan yang dikonstruksikan dalam buku teks kimia, bagaimana pengetahuan tersebut dikonstruksikan dalam teks tersebut dan tingkat keterbacaan teks pedagogik dalam konteks pendidikan menengah Indonesia. Untuk mencapai tujuan, penelitian ini menggunakan studi kasus kualitatif. Teks pedagogik kimia untuk siswa menengah dipilih sebagai data. Data kemudian dianalisis dengan menggunakan kerangka semantik wacana (Hao, 2015, 2018; Martin, 1992; Martin & Rose, 2007) termasuk didalam nya analisis taksonomi dan urutan aktivitas, SF-MDA untuk gambar visual (Martin & Rose, 2008), dan SF-MDA untuk simbolisme kimia (Liu, 2011; Liu & Taber, 2016). Studi ini menemukan bahwa jenis pengetahuan atau field yang dipakai dalam teks pedagogik adalah bidang domestic, specialised, dan exploration yang diwujudkan melalui bahasa, gambar, dan simbolisme kimia. Domestic field ditafsirkan melalui taksonomi yang dibentuk oleh entitas benda domestik. Specialised field diwujudkan melalui urutan operatif dan taksonomi utilitarian dan exploration field dalam teks ini diwujudkan melalui urutan implikasi dan taksonomi teknis yang disusun oleh entitas trained gaze. Berdasarkan perhitungan online Automated Readability Index, skor teks untuk sekolah menengah pertama adalah 10.7 yang berarti bahwa teks tersebut dirancang untuk siswa pada usia 15-17 tahun. Sementara itu, skor teks untuk siswa SMA adalah 11,5. Kedua skor menunjukkan bahwa beberapa potensi kesulitan untuk membaca teks ditemukan di antara siswa kelas tujuh dan kesepuluh dalam konteks pendidikan Indonesia. Temuan ini menunjukkan bahwa instruksi eksplisit harus diberikan kepada siswa untuk memahami simbol.;The present study investigates the types of knowledge constructed in the chemistry textbooks, how such knowledge is constructed in the texts and the level of readability of the pedagogic texts in an Indonesian secondary education context. To achieve the objectives, this study used a qualitative case study. The chemistry pedagogic texts for middle school (junior and high school students) were selected as data. The data were then analysed by using Systemic Functional and Legitimation Code Theory, particularly taxonomy and activity sequence (Hao, 2015, 2018; Martin, 1992; Martin & Rose, 2007) as well as LCT's semantics, SF-MDA for visual images (Martin & Rose, 2008), and SF-MDA for chemical symbolisms (Liu, 2011; Liu & Taber, 2016). The study found that the knowledge or field that is instantiated in the pedagogic texts is domestic, specialised, and exploration fields which are realised through language, images, and chemical symbolisms. The domestic field is construed through a taxonomy constituted by domestic entity. The specialised field is realised through operative sequences and utilitarian taxonomy and the exploration field in this text is realised through implication sequences and technical taxonomy composed by trained-gaze entity. Based on the online calculation of Automated Readability Index, the score of the text for junior high school is 10.7 which means that the text is designed for students at age of 15-17 years old. Meanwhile, the score of the text for senior high school students is 11.5. Both scores indicate that some difficulty potentials to read the texts was found among seventh and tenth graders in Indonesian education context. This findings suggest that explicit instructions should be given to the students to understand the symbols.